Colorectal premalignancy is associated with consensus molecular subtypes 1 and 2. (23rd August 2018) - Chang, K; Willis, J A; Reumers, J; Taggart, M W; San Lucas, F A; Thirumurthi, S; Kanth, P; Delker, D A; Hagedorn, C H; Lynch, P M; Ellis, L M; Hawk, E T; et al.
Abstract: Background: Gene expression-based profiling of colorectal cancer (CRC) can be used to identify four molecularly homogeneous consensus molecular subtype (CMS) groups with unique biologic features. However, its applicability to colorectal premalignant lesions remains unknown. Patients and methods: We assembled the largest transcriptomic premalignancy dataset by integrating different public and proprietary cohorts of adenomatous and serrated polyps from sporadic ( N = 311) and hereditary ( N = 78) patient populations and carried out a comprehensive analysis of carcinogenesis pathways using the CMS random forest (RF) classifier. Results: Overall, transcriptomic subtyping of sporadic and hereditary polyps revealed CMS2 and CMS1 subgroups as the predominant molecular subtypes in premalignancy. Pathway enrichment analysis showed that adenomatous polyps from sporadic or hereditary cases (including Lynch syndrome) displayed a CMS2-like phenotype with WNT and MYC activation, whereas hyperplastic and serrated polyps with CMS1-like phenotype harbored prominent immune activation. Rare adenomas with CMS4-like phenotype showed significant enrichment for stromal signatures along with transforming growth factor-β activation. There was a strong association of CMS1-like polyps with serrated pathology, right-sided anatomic location and BRAF mutations. Conclusions: Based on our observations made in premalignancy, we propose a model of pathway activation associated with CMS classification in colorectal carcinogenesis. Specifically, while adenomatous polyps are largely CMS2, most hyperplastic and serrated polyps are CMS1 and may transition into other CMS groups during evolution into carcinomas. Our findings shed light on the transcriptional landscape of premalignant colonic polyps and may help guide the development of future biomarkers or preventive treatments for CRC.